2009
DOI: 10.1159/000202822
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/Nitrative Modifications of Plasma Proteins and Thiols from Patients with Schizophrenia

Abstract: Objective: The level of various specific biomarkers of oxidative stress in plasma from schizophrenic patients, as well as biomarkers (the level of isoprostanes) in urine in schizophrenic patients was described. The aim of our present study was to evaluate biomarkers of oxidative stress by oxidative/nitrative modifications of plasma proteins (by measuring the level of carbonyl groups and 3-nitrotyrosine in proteins) from patients with schizophrenic disorders and from control group. We also investigated the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 66 publications
7
36
1
Order By: Relevance
“…The enzyme GSH-Px then regenerates GSH from GSSG with NADPH as a source of hydrogen. In the present study erythrocyte GSH concentration and the activity of GSH-Px were significantly reduced in shizophrenic subjects with the three major symptoms, this was in agreement with recent studies 12,13,15,30 in which they reported decreased activity of GSH-Px in schizophrenic patients; likewise, other researchers 35,38,39 reported reduction in concentration GSH in their studies. CAT activity is one of the most important mechanisms by which RBC dispose of H 2 O 2 produce by dismutation reaction of O 2 in a cell.…”
Section: Discussionsupporting
confidence: 93%
“…The enzyme GSH-Px then regenerates GSH from GSSG with NADPH as a source of hydrogen. In the present study erythrocyte GSH concentration and the activity of GSH-Px were significantly reduced in shizophrenic subjects with the three major symptoms, this was in agreement with recent studies 12,13,15,30 in which they reported decreased activity of GSH-Px in schizophrenic patients; likewise, other researchers 35,38,39 reported reduction in concentration GSH in their studies. CAT activity is one of the most important mechanisms by which RBC dispose of H 2 O 2 produce by dismutation reaction of O 2 in a cell.…”
Section: Discussionsupporting
confidence: 93%
“…Clinical trials demonstrated increased total plasma peroxide [89] and serum NO levels in schizophrenic patients [90]. The increased levels of plasma MDA [89,[91][92][93][94], thiobarbituric acid reactive substances (TBARS) [95] and isoprostanes in urine [95], higher levels of 3-nitrotyrosine in plasma [96] and increased DNA [97,98] and RNA damage [98] were also observed.…”
Section: Clinical Studiesmentioning
confidence: 96%
“…Schizophrenia is also associated with oxidative/nitrative stress [2][3][4][5][6][7][8][9][10][11][12][13]. Moreover, in schizophrenia, oxidative stress may be induced by treatment of antipsychotic drugs [14,15].…”
Section: Introductionmentioning
confidence: 99%